HUBUNGAN ANTARA PENGAWASAN DAN LINGKUNGAN KERJA DENGAN EFEKTIVITAS KERJA PEGAWAI KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI SULAWESI UTARA - TRI SUSANTI (Jurnal Manajemen Pendidikan, 2011)
This research aims to determine the relationship between (1) controlling with work effectiveness, (2) work environment with work effectiveness, and (3) the relationship between controlling and work environment with work effectiveness altogether. Methods this research used a survey with the correlation approach. The sample of this research use 60 responden, and 20 responden for testing, and selected based on simple random sampling. Study toward regional office employees ministry religion province North Celebes.The technique of data collecting was using the instrument in the form of questionnaire. This instrument is calibrated with the test item validity and reliability coefficients. To test the validity of three variables (controlling, work effectiveness and work environment) using Pearson Product Moment correlation, while the reliability coefficient is calculated three variables (controlling, work effectiveness and work environment) using the formula of Cronbach Alpha. The results of this research are first, there are positive relationships between controlling and work effectiveness, which can be given on the correlation coefficient with the regression equation. Secondly, there is a positive relationship between work environment with work effectiveness that can be given on regression correlation coefficient with regression equation. Third, there is a positive relationship between controlling and work environment together with work effectiveness, which can be given on the correlation coefficient by multiple regression equation.